2012
DOI: 10.1002/uog.11144
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cerebrovascular resistance and neonatal EEG predict 18‐month neurodevelopmental outcome in infants with congenital heart disease

Abstract: Objectives The purpose of this study was to investigate early markers of risk for neurobehavioral compromise in congenital heart disease (CHD) survivors. Methods Fetuses < 24 wks gestational age (GA) were enrolled in this prospective pilot study for serial Doppler assessment of the middle cerebral and umbilical artery. The cerebral-to-placental resistance ratio (CPR) and MCA pulsatility index (PI) z-scores for GA were calculated. After birth, subjects underwent high-density (128-lead) electroencephalogram (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 19 publications
4
64
0
2
Order By: Relevance
“…Additionally, studies linking cerebral Doppler abnormalities to impaired neurodevelopment in the growth-restricted population focus on third-trimester fetuses, with evaluation a few weeks from delivery being most predictive of outcomes, and our subjects were studied in the second trimester. A study by Williams et al 48 found cerebroplacental Doppler abnormalities before 23 weeks' gestation to be predictive of impaired postnatal neurodevelopment in fetuses with congenital heart disease. Aghajanian et al 36 evaluated MCA PI in fetuses with TTT, and found that RTs had lower MCA PI Z scores compared with DTs, which was found to increase significantly after laser therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, studies linking cerebral Doppler abnormalities to impaired neurodevelopment in the growth-restricted population focus on third-trimester fetuses, with evaluation a few weeks from delivery being most predictive of outcomes, and our subjects were studied in the second trimester. A study by Williams et al 48 found cerebroplacental Doppler abnormalities before 23 weeks' gestation to be predictive of impaired postnatal neurodevelopment in fetuses with congenital heart disease. Aghajanian et al 36 evaluated MCA PI in fetuses with TTT, and found that RTs had lower MCA PI Z scores compared with DTs, which was found to increase significantly after laser therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Doppler ultrasound is an emerging technique that can predict brain volumetric abnormalities and neurodevelopmental outcomes of fetuses with certain CHDs [15,4550]. This noninvasive technique offers important information regarding fetal hemodynamics by measuring the velocity of blood flow through cerebral arteries.…”
Section: Neuroimaging Of White Matter In Chd Patientsmentioning
confidence: 99%
“…Williams et al (2012b) señalan que con este tipo de intervención se reducen las tasas de mortalidad en estos infantes pero que, a su vez, aumenta la probabilidad de que aparezcan morbilidades en el neurodesarrollo a largo plazo, según defiende Schaefer et al (2013).…”
Section: Introductionunclassified
“…Junto a ellos, Williams et al (2012b) recomiendan y consideran que es conveniente que estos niños reciban AT, pues varios autores han encontrado en recién nacidos a término con cardiopatías congénitas, patrones de desarrollo similares a los niños prematuros (Esquivel et al 2013). Estos últimos reciben AT (GAT, 2000) mientras que los primeros no, a pesar de que les beneficiaría, según indican Williams et al (2012b).…”
Section: Introductionunclassified